2005
DOI: 10.1593/neo.05235
|View full text |Cite
|
Sign up to set email alerts
|

Hypermethylation of the TPEF/HPP1 Gene in Primary, Metastatic Colorectal Cancers

Abstract: The role of promoter methylation in the process of cancer cell metastasis has, however, not yet been studied. Recently, methylation of the TPEF (transmembrane protein containing epidermal growth factor and follistatin domain) gene was reported in human colon, gastric, and bladder cancer cells. Using the Methylight assay, TPEF/HPP1 gene methylation was assessed in primary colorectal cancers (n = 47), matched normal colon mucosa, as well as in the liver metastasis of 24 patients with colorectal cancer, and compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 25 publications
3
34
1
Order By: Relevance
“…Thus, quantitative assessment of DNA methylation is very important. 24,25,27,39,40 Our findings provide additional supporting evidence for molecular features of CIMP-low tumors different from CIMP-high and CIMP-0 tumors. CIMP-low tumors generally appear to methylate at multiple CIMP-specific CpG islands at low levels, whereas CIMP-0 tumors tend to show more loci with no evidence of methylation and CIMP-high tumors tend to show more loci with high-level methylation.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Thus, quantitative assessment of DNA methylation is very important. 24,25,27,39,40 Our findings provide additional supporting evidence for molecular features of CIMP-low tumors different from CIMP-high and CIMP-0 tumors. CIMP-low tumors generally appear to methylate at multiple CIMP-specific CpG islands at low levels, whereas CIMP-0 tumors tend to show more loci with no evidence of methylation and CIMP-high tumors tend to show more loci with high-level methylation.…”
Section: Discussionsupporting
confidence: 67%
“…MethyLight assays (quantitative methylation-specific PCR) are robust and reproducible in quantifying methylation in DNA from paraffinembedded tumor tissue. [21][22][23][24][25][26][27] Low index of methylation in MethyLight analysis is not associated with gene silencing, 24 indicating that low methylation index in MethyLight indeed reflects low-level DNA methylation.…”
mentioning
confidence: 99%
“…HPP1 has been previously reported to be methylated in adenocarcinomas from the esophagus, stomach, small bowel and colorectum. [26][27][28][29][30][31] A previous study found HPP1 to be downregulated in fibrolamellar carcinomas at the mRNA level 10 and the current results demonstrate that the downregulation of HPP1 expression is associated with promoter methylation. The function of this gene is unknown; however, it codes for a transmembrane protein that contains both epidermal growth factor and follistatin-like domains and may play a role in inhibiting serine proteases.…”
Section: Figuresupporting
confidence: 58%
“…It has been shown that these three genes can be methylated in patients with CRC and precancerous lesions [6][7][8][12][13][14][15][16] . Of the genes chosen for this study, SFRP2 gene belongs to a new class of tumor suppressor genes (SFRPs), which are secreted glycoproteins working as inhibitory modulators of a putative tumorigenic pathway (the Wnt signaling pathway).…”
Section: Discussionmentioning
confidence: 99%